Edukasi Masyasrakat dalam Mengurangi Rabies Serta Peningkatan Kesehatan Ternak melalui Pemeriksaan Masal pada Lima UPT di Kabupaten Agam, Sumatera Barat - Arif Yahya; Muhammad Ihsan; Alvin Jefry; Agus Setiyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Rabies is a deadly disease transmitted from animals to humans with more than 59,000 people recorded or almost 1 death every 9 minutes CDC (2017). The main source of transmitting rabies is dogs through bites and saliva which contain viruses. Rabies is a strategic infectious animal disease (PHMS) whose existence is prioritized to be controlled in Indonesia. West Sumatra Province is still an area that is not yet free of rabies with extraordinary events (KLB). Aside from rabies, the biggest challenge is the many diseases of Jembrana. Jembrana is a strategic disease with its main host being only Bali cattle (Bos sondaicus). Decreased immune system cells (B lymphocytes) will cause the development of bacteria in the body's organs or sekuder infection (Directorate of Animal Health 2015). Thus causing losses including livestock mortality, declining health and quality of livestock, disruption of activities involving cattle, to the loss of closure of the affected area. Implementation of activities in the form of socialization and education about rabies, rabies vaccination, and mass animal health checks. The results of the field show that the number of treatments for livestock is 931, HPR vaccination, 1,211 and 859 people have received socialization regarding the spread of rabies in 5 UPTs in Agam District. Education and assistance are given to the public about the importance of eradicating rabies. The spread of jembrana disease can be inhibited by using vaccines through mass treatment programs. Key words: education, livestock, rabies, vaccines